2006
DOI: 10.3346/jkms.2006.21.2.374
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Pfeiffer Syndrome

Abstract: Pfeiffer Syndrome is as rare as Apert syndrome in the Western population. This condition is very rare in the Asian population and has not been previously reported in Korea. The authors report with a review of literature the case of a newborn baby with Pfeiffer syndrome, manifested by bicoronal craniosynostosis, broad thumbs, and big toes. The infant also had bilateral syndactyly of the fingers and toes, mild proptosis, choanal hypoplasia and maxillary hypoplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Th e prenatal diagnosis of cranial deformities (Park et al 1996) is associated with diverse syndromes: a strawberry-shaped cranium is associated with trisomy 18 (T18); a lemon-shaped cranium with neural tube defects; frontal prominence with achondroplasia and the Russell -Silver syndrome; trigonocephaly with Jacobsen syndrome; brachycephaly with trisomy 21 (T21); chondrodysplasia, the Cornelia de Lange syndrome and cranial asymmetry with amniotic band syndrome and the Wolf -Hirschhorn syndrome. A cloverleaf-shaped cranium is present in thanatophoric dysplasia (not associated with craniosynostosis); or syndromes that indeed are associated with craniosynostosis such as Apert, Carpenter, Crouzon, Jackson Weiss and Pfeiff er syndromes (Benacerraf et al 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Th e prenatal diagnosis of cranial deformities (Park et al 1996) is associated with diverse syndromes: a strawberry-shaped cranium is associated with trisomy 18 (T18); a lemon-shaped cranium with neural tube defects; frontal prominence with achondroplasia and the Russell -Silver syndrome; trigonocephaly with Jacobsen syndrome; brachycephaly with trisomy 21 (T21); chondrodysplasia, the Cornelia de Lange syndrome and cranial asymmetry with amniotic band syndrome and the Wolf -Hirschhorn syndrome. A cloverleaf-shaped cranium is present in thanatophoric dysplasia (not associated with craniosynostosis); or syndromes that indeed are associated with craniosynostosis such as Apert, Carpenter, Crouzon, Jackson Weiss and Pfeiff er syndromes (Benacerraf et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Pfeiff er syndrome was fi rst described by Pfeiff er in 1964 (Park et al 1996) and then by Cohen in 1993, based on phenotype severity, describing three types: Type I, Type II and Type III. Type I is associ- ated with mild manifestations, having normal neurological development and a good prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that cases with Type 1 PS have good prognosis. Patients with Type 2 and Type 3 prognosis have reported early death in spite of aggressive medical and surgical treatment [1]. Our case was Type 1 PS and the clinical findings were relatively acceptable in comparison with other types.…”
Section: Discussionmentioning
confidence: 53%
“…Pfeiffer's syndrome (PS) is a rare, autosomal dominant, variableseverity acrocephalic skull characterized by Pfeiffer in 1964, characterized by a declined midface, hands and feet, and large thumb and large foot syndactyly [1]. PS is characterized by the appearance of skull and leg anomalies in eight individuals from three quadrants [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation